The esophageal rapunzel syndrome: a case of a trichobezoar in the esophagus - Ağar, Mehmet; Çelik, Muhammet Reha; Ulutaş, Hakkı; Gülçek, İlham; Kalkan, Muhammed (Emergency Care Journal, 2023)
Rapunzel syndrome is a form of trichobezoar, a rare form of bezoar, especially seen in individuals with hair pulling (trichotillomania) and hair eating (tricophagia) habits, that extends from the pylorus into to the duodenum, jejunum and even the colon. We report the case of a 37-year-old woman with a trichobezoar in the esophagus, causing esophageal rupture that required an urgent surgical intervention.